PENGARUH KREDIBILITAS NARASUMBER BERITA POLITIK TERHADAP INTERNALISASI NILAI BERITA POLITIK PADA MASYARAKAT - Ida Wiendijarti (Jurnal Ilmu Komunikasi, 2008)
They usage of various newscources for political news is sometimes confiousing, misleading and giving uncertainty to public. This conditions has resulted in the deman of the press to be more credible in representing news with political dimensions. To present to credible political news, it is nessesary to pay attentions on the selection of credible new scources in relation to obtain public trust. The problem statement in this research was to identity whether there was significant influence between the credibility of political newscources toward the internalization of political news value within the public. The research shows positive and significant correlations between the credibility of political new scources toward the internalizations within public. Intelectual was the highers influenced newscources for political news, followed by beaurocrats and political elites as the latest.